Social Cohesion and Labor Mobility - Klaus F. Zimmermann (Global Labor Organization (GLO), 2018)
Social cohesion and labor mobility both have the same objective and do not need to be in conflict. They are about cooperating among individuals and societies in order to survive and prosper. Social cohesion can benefit from labour mobility: Labour mobility is economically beneficial for migrants and natives. Attitudes towards migrants are more friendly if they come and work. Migrants are more accepted if they are many. The wellbeing of natives is higher with more migrants present.
Keywords: F22; J61; M14; 330; labor mobility; social cohesion; wellbeing; attitudes towards migrants; equality